Experimental analysis of genetic algorithm-enhanced PI controller for power optimization in multi-rotor variable-speed wind turbine systems - Habib Benbouhenni; Nicu Bizon; Mourad Yessef; Z. M. S. Elbarbary; Ilhami Colak; Badre Bossoufi; Abdulrahmane Al Ayidh (Scientific Reports)
Abstract The direct power control (DPC) algorithm is one of the most popular linear techniques used to implement notable controllers, known for their simplicity and fast dynamic response. However, this approach has drawbacks that cause a decrease in the current quality and disturbances in the network. Therefore, this experimental work presents a simple and efficient solution that uses a proportional-integral regulator based on a genetic algorithm to regulate the power quality. The designed approach uses a pulse width modulation to produce control pulses for the operation of the rotor inverter of a doubly-fed induction generator-based multi-rotor wind system. This approach is first verified in MATLAB using a 1500 kW generator operating under different working conditions. Furthermore, the processor-in-the-loop (PIL) test using dSPACE 1104 is used to verify the efficacy and ability of the designed approach in enhancing the effectiveness of the power system under study. The results obtained in all tests demonstrate that compared to DPC, the designed approach reduces active power ripples with estimated percentages of 71.42%, 66.67%, and 70%, and the reactive power overshoot value is reduced with estimated percentages of 92.85%, 56.48%, and 79.21%. In addition, the experimental results (using the PIL test) confirm the ability of the designed control algorithm to enhance the energy and current quality, which makes this designed technique a suitable solution in the field of control.